A COMPARATIVE STUDY ON SOME PROPERTIES AND OXIDATION STABILITY DURING STORAGE OF BUTTER PRODUCED FROM DIFFERENT ANIMALS' MILK - Çakmakçi, Songül; Tahmas Kahyaoğlu, Deren (The Association of Food Technology, 2017)
In this study, butter producedfrom cow, sheep and goat cream and was examined during a 90 day storage periodat 4°C. A total of 42 samples produced and were analysed at 1st, 15th,30th, 45th, 60th, 75th and 90thdays. It was found that butter type and storage period had significant effecton the pH value, titratable acidity, acid value, fat constants, peroxide andthiobarbituric acid values, β-carotene and vitamin A amounts of the buttersamples. The pH value, iodine number, b value and vitamin A amountsdecreased during the storage in all the types of butter, whereas titratableacidity, acid value, Reichert-Meissl, Polenske and saponification numbers andoxidation increased. β-carotene was detected only in butter produced from cowmilk creams which decreased during storage. Sensory analysis points decreasedin all the butter samples during the storage the highest point belonging to thebutter produced from cows’ milk.

Bu araştırmada, inek, koyun vekeçi sütü kremasından üretilen tereyağları, 4°C’de 90 günlük muhafaza süresinceincelendi. Toplam 42 tereyağı örneği 1., 15., 30., 45., 60., 75. ve 90.günlerde analiz edildi. Tereyağı çeşidi ve depolama süresinin, tereyağı örneklerininpH değeri, titrasyon asitliği, asit değeri, yağ sabitleri, peroksit vetiyobarbitürik asit değerleri, β-karoten ve A vitamini miktarları üzerindeönemli etkisi olduğu bulundu. pH değeri, iyot sayısı, b değeri ve Avitamin miktarı bütün tereyağı örneklerinde depolama süresince azalırken,titrasyon asitliği, asit değeri, Reichert-Meissl, Polenske ve sabunlaşmasayıları ve oksidasyon tüm tereyağı çeşitlerinde depolama süresince arttı.β-karoten sadece inek sütü kremasından üretilen tereyağında bulundu. Bütüntereyağı örneklerinde depolama süresince duyusal puanlar azaldı, en yüksekpuanları inek sütünden üretilen tereyağları aldı.
Keywords: Tereyağı; Oksidasyon stabilitesi; Vitamin; Depolama; Butter; Oxidation stability; Vitamin; Storage; 2. Zero hunger